Efficient Regular Graph Generalized Neighbor Designs - Mehmood, Q.; Abbas, Z.; Shehzad, F.; Ahmed, R. (The Nucleus, 2020)
In this study we have constructed a class of economical block designs called regular graph generalized neighbor designs for circular blocks of size 4 and v â‰¤ 50. This class of design can provide an efficient alternative of universally optimal neighbor designs. These designs will increase the applications of regular graph designs particularly in the fields of serology, agro forestry and agriculture, etc. In terms of efficiency factor, proposed designs are more efficient as compared with other generalized neighbor designs. The two best designs, for v =26 and v =50, have percentage of upper bound 99.91% and 99.93% respectively. Â 